Development through rupture: Trauma literature as emotional development tool. What effects does reading trauma literature have on the emotional development of A-level students? - Gibbons, D (2019)
Background Emotional development involves "mastering" experiences. In order to master experience, young adults have to construct an identity, through which experience is organised on an autobiographical framework. Although traumatic experiences may seem counter to the idea of emotional development, traumatic experience filtered through literature has been previously explored in education as a potential avenue for developing students· empathy and resilience. In its attempts to represent terrifying experience, trauma literature exhibits how narrative tools can be applied to traumatic experience to help master it. My aim is explore the effects reading trauma literature has on emotional development. Reading trauma literature may be useful for emotional development through supporting identity formation.